THE REVALUATION POTENTIAL OF UKRAINIAN AGRICULTURAL EXPORTS IN THE CONTEXT OF MARTIAL LAW AND POST-WAR RECOVERY - KOVALENKO, Victoria; SHELUDKO, Serhii (Journal of European Economy, 2024)
The paper highlights the immediate and delayed impact of certain factors on the exchange rate dynamics in Ukraine. It is proved that exports of food products and raw materials for their production can significantly strengthen the national currency in the long run. Continuous growth in food exports helps to slow down exchange rate appreciation, which ultimately leads to a stronger national currency. Thus, a strategy of focusing on increasing food exports can play an important role in strengthening the Ukrainian currency in the long run, having a positive impact on exchange rate dynamics and contributing to overall economic stability. The study reveals the understanding of the complex relationship between war, food security, and economic stability. Furthermore, the analysis adds a new dimension to the debate on the strategic importance of the agricultural sector for foreign exchange reserves and foreign exchange accumulation. Understanding the relationship between export volumes, world prices, and exchange rate fluctua tions can help to better predict and manage currency fluctuations and to determine the extent to which Ukraine’s revolving fund capacity can be built. JEL: Q17; F31; O24.